The Impact of COVID-19 Pandemic on Country Risk: An Empirical Evidence from Egypt Vs. UK - Barakat, Hanan Amin; Moawad, Rania Ramadan (The Arab Journal of Administration, 2025)
This paper aims to examine the impact of the COVID-19 pandemic on the country risk in Egypt and the Uk in parallel with control variables; nominal effective exchange rate, and inflation rate. The vector error correction model (VECM) method is used in the study to examine both the short and long-term relationships between the variables over the period stating from February 2020 until June 2021 on a monthly basis. The study employs government bond spread yield as a proxy for country risk measures. For Egypt Model, The empirical findings showed that as the ECT coefficient is negligible, there is no long-run significant relationship between the covid-19, the exchange rate, and the country risk. Moreover, there is no relationship between COVID-19 and country risk, although there is a short-run relationship between the exchange rate and country risk. Whereas for UK model, the ECT coefficient is negative and significant, the investigation discovers a long-run significant relationship between the covid-19, the exchange rate, the inflation rate, and the country risk. In the short term, there is a relationship between inflation rate and country risk, but there is none between covid-19, exchange rate, and country risk.